Goldfrank's toxicologic emergencies - Nelson, Lewis 1963-; Smith, Silas W.; Hoffman, Robert S.; Howland, Mary Ann; Goldfrank, Lewis R.; Lewin, Neal A.; Flomenbaum, Neal E. (New York McGraw-Hill Education, 2019)
"Goldfrank's Toxicological Emergencies is a multi-authored text of more than 2000 pages prepared by utilizing the education and management principles we apply at the New York City Poison Center and at our clinical sites. In this ninth edition of Goldfrank's Toxicological Emergencies, we proudly offer readers an approach to medical toxicology using evidence based principles viewed through a lens of bedside clinical practice" -- Provided by publisher.
Part A. The general approach to the patient -- Part B. The fundamental principles of medical toxicology -- Section 1. Biochemical and molecular concepts -- Section 2. Pathophysiologic basis: organ systems -- Section 3. Special populations -- Part C. The clinical basis of medical toxicology -- Section 1a. Analgesics and antinflammatory medications -- 1b. Food, diet, and nutrition -- 1c. Pharmaceuticals -- 1d. Antimicrobials -- 1e. Cardiopulmonary medications -- 1f. Anesthetics and related medications -- 1g. Psychotropic medications -- 1h. Substances of abuse -- 1i. Metals -- 1j. Household products -- 1k. Pesticides -- 1i. Natural toxins and envenomations -- 1m. Occupational and environmental toxins -- 1n. Disaster preparedness -- Part D: Population health -- Section 1. Poison control centers, health systems, and epidemiology -- Section 2. Legal aspects of toxicology.
Includes bibliographical references and index.
Keywords: Emergencies; Poisoning; Poisons; Emergencies; Poisoning; Poisons; Toxicological emergencies; Toxicological emergencies -- Case studies; Emergencies -- Case studies; Poisoning -- Case studies; Poisons -- Case studies; Emergencies; Poisoning; Poisons